2006
DOI: 10.1007/s10519-006-9089-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of Aggressive Behavior in Golden Retriever Dogs with a Questionnaire

Abstract: Reliable and valid phenotyping is crucial for our study of genetic factors underlying aggression in Golden Retriever dogs. A mail questionnaire based on the Canine Behavioral Assessment and Research Questionnaire (CBARQ; Hsu and Serpell, 2003, JAVMA 223(9):1293-1300) was used to assess behavioral phenotypes. Owners of 228 Golden Retrievers completed the questionnaire. These dogs had been referred to our clinic for aggression problems several years earlier or they were related to aggressive dogs. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 23 publications
2
23
0
4
Order By: Relevance
“…In this study, neuter status did not affect the likelihood of human directed aggression in dogs. This finding is consistent with other studies (van den Berg et al 2006;Bennett and Rohlf 2007;Hsu and Sun 2010) but contrasts with mixed results from other reports of both lower aggression in neutered dogs (Borchelt 1983;Wright 1990;Gershman et al 1994;Messam et al 2008), and higher aggression in neutered dogs Serpell 1997a, 1997b;Guy et al 2001a). That males were more likely to show human-directed aggressive behaviours in this study, yet entire males had no greater risk than neutered ones, may be related to testosterone 'priming' of the brain in young animals, or because some male dogs may have been neutered because of aggression and/or medical reasons.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, neuter status did not affect the likelihood of human directed aggression in dogs. This finding is consistent with other studies (van den Berg et al 2006;Bennett and Rohlf 2007;Hsu and Sun 2010) but contrasts with mixed results from other reports of both lower aggression in neutered dogs (Borchelt 1983;Wright 1990;Gershman et al 1994;Messam et al 2008), and higher aggression in neutered dogs Serpell 1997a, 1997b;Guy et al 2001a). That males were more likely to show human-directed aggressive behaviours in this study, yet entire males had no greater risk than neutered ones, may be related to testosterone 'priming' of the brain in young animals, or because some male dogs may have been neutered because of aggression and/or medical reasons.…”
Section: Discussionsupporting
confidence: 94%
“…The sample size of each study varied considerably, ranging from 7 dogs [59] to 938 dogs [35], with an average of 84 dogs per study. The time interval between measures across studies varied as well, ranging from 3 days [83] to 224 weeks [37], with an average interval of 21 weeks. The age at which a dog was first tested also varied considerably across studies, ranging from 3 weeks of age [84] to 296 weeks of age [85], with a mean of 49 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…When compared with the previous reports, the novelty of this study lies in the fact that individual high values of heritability reported either for individual trait or traits within a study (e.g., FĂ€lt et al, 1982;Goddard and Beilharz, 1985;Kreiner et al, 1992;Schmutz and Schmutz, 1998;Wilsson and Sundgren, 1998;van den Berg et al, 2006b;Liinamo et al, 2007), or for a single dog breed (Kreiner et al, 1992;Schmutz and Schmutz, 1998) disappeared when statistical synthesis of the data across studies was applied. The occasional high values of heritability, shown for example in Figs.…”
Section: Discussionmentioning
confidence: 95%